Existence and ulam stability of k-generalized ψ-Hilfer fractional problem - Lazreg, Jamal Eddine; Benchohra, Mouffak; Salim, Abdelkrim (Journal of Innovative Applied Mathematics and Computational Sciences, 2022)
In this paper, we prove existence, uniqueness stability results for a class of initial value problem for fractional differential equations involving generalized ψ-Hilfer fractional derivative. The result is based on the Banach contraction mapping principle. In addition, two examples are given to illustrate our results.